Tris(oxalato)chromate(III) hybrid salts templated by pyridinium and mixed pyridinium-ammonium cations: synthesis, structures and magnetism. Issue 8 (7th May 2021) - Choubeu, Coustel M. N.; Ndosiri, Bridget N.; Vezin, Hervé; Minaud, Claire; Orton, James B.; Coles, Simon J.; Nenwa, Justin
Abstract: By modifying the stoichiometric ratio of starting materials, two tris(oxalato)chromate(III) salts, (C7 H11 N2 )3 [Cr(C2 O4 )3 ] (1 ) and (C5 H8 N3 )2 (NH4 )[Cr(C2 O4 )3 ]·2H2 O (2 ) (C7 H11 N2 ) + = 2-amino-4, 6-dimethylpyridinium, (C5 H8 N3 ) + = 2, 6-diaminopyridinium, were synthesized and characterized by elemental and thermal analyses, single-crystal X-ray diffraction, IR and UV − Vis spectroscopies, EPR and SQUID measurements. Salt 1 exhibits a 3-D supramolecular framework based on [Cr(C2 O4 )3 ] 3- and 2-amino-4, 6-dimethylpyridinim cations, (C7 H11 N2 ) +, via N–H···O hydrogen bonds. Interestingly, π–π stacking interactions between pyridine rings contribute to the stabilization of the crystal packing. In contrast to salt 1, no π–π stacking interactions are observed in the mixed-cation salt 2 and its crystal packing is consolidated by N–H···O and O − H···O hydrogen bonds. EPR spectra of 1 and 2 are consistent with the oxidation state +3 of the chromium center in an octahedral environment. Temperature-dependence of the magnetic susceptibility data investigated from 2 to 300 K revealed the existence of zero-field splitting effects (ZFS) for Cr(III) ions in both compounds. Graphical Abstract: